Recent advances in the diagnosis of Schistosoma infection: the detection of parasite DNA - Rabello Ana; Pontes Luís André; Dias-Neto Emmanuel (Memorias do Instituto Oswaldo Cruz, 2002)
As Schistosoma sp. control programs are chiefly based on treatment of infected population, adequate case finding has a crucial role. The available diagnostic methods are far from ideal, since the search for eggs in stools and the detection of circulating antigens lack sensitivity in low prevalence and post-treatment situations and antibody detection lacks specificity. In most endemic foci, repeated treatment of infected people leaves a number of non-diagnosed and consequently non-treated persons, enough to maintain a persistent residue of 5 to 10% prevalence. In an attempt to surpass these diagnostic limitations we have developed a polymerase chain reaction (PCR) for the detection of Schistosoma sp. in feces that, in a first population study, has shown to be more sensitive than three-repeated stool Kato-Katz examination. The PCR may constitute a valuable tool for the diagnosis of the Schistosoma sp. infection in special situations, when high sensitivity and specificity are required and infrastructure is available.